Pengembangan e-LKPD Menggunakan Wizer.me pada Materi Sistem Persamaan Linear Dua Variabel SPLDV di SMP Negeri 3 Malangke Barat: Pengembangan e-LKPD Menggunakan Wizer.me pada Materi Sistem Persamaan Linear Dua Variabel SPLDV di SMP Negeri 3 Malangke Barat - Zulfahmi Muassar Gita Asarani; Rosdiana; Irma T; Sitti Zuhaerah Thalhah; Mifta Zulfahmi Muassar (Qalam : Jurnal Ilmu Kependidikan, 2026)
This study aimed to develop an electronic student worksheet (e-LKPD) using Wizer.me on the topic of Two-Variable Linear Equation Systems (SPLDV) for eighth-grade students at SMP Negeri 3 Malangke Barat. This research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were 21 eighth-grade students. Data were collected through observation, interviews, documentation, questionnaires, and learning outcome tests. The developed product was validated by media and material experts, then tested for practicality and effectiveness. The results showed that the e-LKPD was categorized as very valid, with a media expert validation score of 90.33% and a material expert validation score of 87.25%. The practicality test results also indicated that the product was very practical, with student responses reaching 85.71% and teacher responses reaching 83.33%. In terms of effectiveness, all students achieved mastery learning with a completion rate of 100%. These findings indicate that the Wizer.me-based e-LKPD is valid, practical, and effective for use in mathematics learning, especially on the topic of SPLDV. Therefore, this product is feasible to be implemented as an innovative digital learning medium in junior high schools